Barriers and Facilitators to Scientific Writing Among Applied Epidemiologists. Issue 3 (May 2017) - Pittman, Jessica; Stahre, Mandy; Tomedi, Laura; Wurster, Jessica
Abstract : Context: Communication in the form of written and oral reports and presentations is a core competency for epidemiologists at governmental public health agencies. Many applied epidemiologists do not publish peer-reviewed articles, limiting the scientific literature of best practices in evidence-based public health. Objectives: To describe the writing and publishing experiences of applied epidemiologists and identify barriers and facilitators to publishing. Design: Telephone focus groups and an 18-question multiple-choice and short-answer Web-based assessment were fielded in 2014. Setting and Participants: Six focus groups composed of 26 applied epidemiologists and an online assessment answered by 396 applied epidemiologists. Sample selection was stratified by years of experience. Main Outcome Measures: Past publishing experience, current job duties as related to publishing, barriers and facilitators to writing and publishing, and desired training in writing and publishing were assessed through focus groups and the online assessment. Results: Focus groups identified 4 themes: job expectations, barriers to publishing, organizational culture, and the understanding of public health practice among reviewers as issues related to writing and publishing. Most respondents (80%) expressed a desire to publish; however, only 59% had published in a peer-reviewed journal. An academic appointment (among doctoral educated respondents) was identified as a facilitator to publishing as was access to peer-reviewed literature. Time (68%) was identified as the greatest barrier to writing and publishing. Other major barriers included lack of encouragement or support (33%) within the public health agency and agency clearance processes (32%). Assistance with journal selection (62%), technical writing skills (60%), and manuscript formatting (57%) were listed as the most needed trainings. Conclusion: Public health agencies can be facilitators for epidemiologists to contribute to the scientific literature through increasing access to the peer-reviewed literature, creating a supportive environment for writing and publishing, and investing in desired and needed training. The results have implications for modifying workplace policies surrounding writing and publishing.